P704 Mechanical complications of acute myocardial infarction in the era of early reperfusion therapy: a case report. (17th January 2020) - Proenca, T; Alves Pinto, R; Martins Carvalho, M; Nunes, A; Araujo, P M; Torres, S; Resende, C X; Grilo, P D; Dias, P; Paiva, M; Casanova, J; Maciel, M J; et al.
Abstract: Introduction: Left ventricular pseudoaneurysm is a rare mechanical complication of myocardial infarction, and its incidence has decreased with the widespread use of reperfusion therapies. Pseudoaneurysm is the result of a free wall rupture contained by pericardial adherences and mural thrombi, which contain the bleeding and prevent cardiac tamponade. Clinical Presentation: A 68-year-old woman who had hypertension, diabetes mellitus and chronic kidney disease (caused by diabetic nephropathy) was first admitted with acute myocardial infarction of the inferior wall. Emergent coronary angiography revealed proximal occlusion of the right coronary artery. Primary angioplasty was performed with three stents implantation. However due to transitory no reflow, verapamil, nitrate and intracoronary abciximab were administered with recovery of coronary flow. Patient remained stable, without recurrence of symptoms. Echocardiography, at discharge, showed normal biventricular function and no mechanical complications. Two months later, the patient was readmitted in the emergency room with constant chest pain, fatigue, prostration and loss of appetite beginning ten days earlier and an episode of syncope. Physical examination revealed fever, cardiac auscultation was rhythmic and without murmurs or pericardial friction rub, and pulmonary auscultation revealed crackles in inferior hemithorax. 12-lead electrocardiogram showed sinus rhythm, Q waves and negative T waves in inferior leads. Blood tests revealed leucocytosis, high sensibility troponin I was 28, 8 ng/L and brain natriuretic peptide was 264, 9 pg/mL. Chest-X-ray demonstrated enlargement of the cardiac silhouette and echocardiography showed moderate to large pericardial effusion with large amounts of fibrin close to right cardiac chambers and a basal inferior pseudoaneurysm with 23 mm x 24 mm; intracavitary contrast was administered without opacification of pericardial space; biventricular function remained normal. Patient was promptly admitted on Cardiac Intensive Care Unit with diagnosis of pseudoaneurysm due to myocardial infarction. Therapeutic with ticagrelor was suspended and surgical correction was proposed, after discussion in Heart Team. False aneurysm correction was performed with a bovine pericardial patch without complications, and the patient was discharged asymptomatic eight days later. Conclusion: Even with lower incidence, pseudoaneurysms remains as a potential life-threatening due to its high risk of rupture. Prompt diagnosis, usually with echocardiography and surgical referral are crucial.